Robust control of a hydraulic cylinder using an observer-based sliding mode control: Theoretical development and experimental validation. (February 2020) - Bakhshande, Fateme; Bach, Resida; Söffker, Dirk
Abstract: This paper focuses on the design of an observer-based sliding mode controller (SMC) for nonlinear hydraulic differential cylinder systems affected by uncertainties. These uncertainties include modeling errors, external disturbances, and measurement noise. The aim is to ensure suitable tracking performance and robustness against unknown inputs. The task of system state and unknown input estimation is performed using high gain Proportional-Integral-Observer (PIO). Input-output exact feedback linearization is used to linearize the system model to be applicable for linear PIO structure. Estimation of system states is directly used in calculation of sliding surface. The SMC is utilized for input-output linearized system to provide a desired performance in the presence of uncertainties and to compensate the effects of external disturbances, plant parameter changes, unmodeled dynamics, measurement noise, etc. Parameter selection of SMC is elaborately considered by defining a novel performance/energy criteria. Stability of closed-loop system is established using Lyapunov method. Furthermore, a complete robustness evaluation considering different levels of measurement noise, modeling errors, and external disturbances is investigated. Experimental results validate the advantages of introduced combined approach in comparison with standard SMC and P-controller approaches. Consequently, integration of state and unknown input estimations into the sliding mode structure leads to appropriate disturbance attenuation and increases the system performance robustness.